Pediatric Chordomas: Results of a Multicentric Study of 40 Children and Proposal for a Histopathological Prognostic Grading System and New Therapeutic Strategies. Issue 3 (18th January 2018) - Beccaria, Kévin; Tauziède-Espariat, Arnault; Monnien, Franck; Adle-Biassette, Homa; Masliah-Planchon, Julien; Pierron, Gaëlle; Maillot, Laetitia; Polivka, Marc; Laquerrière, Annie; Bouillot-Eimer, Sandrine; Gimbert, Edouard; Gauchotte, Guillaume; et al.
Abstract: Pediatric chordomas are rare malignant neoplasms, and few data are available for optimizing therapeutic strategies and outcome. This study aimed at evaluating how best to manage them and to identify prognostic factors. This multicentric retrospective study included 40 children diagnosed with chordomas between 1966 and 2012. Clinical, radiological, and histopathological data, treatment modalities, and outcomes were reviewed. The median age was 12 years old. Most chordomas were histologically classical forms (45.5%) and were mostly located at the skull base (72.5%). The overall survival (OS) was 66.6% and 58.6%, and progression-free survival (PFS) was 55.7% and 52% at 5 and 10 years, respectively. Total resection was correlated with a better outcome (p = 0.04 for OS and PFS, log-rank). A histopathological/immunohistochemical grading system recently crafted for adults was applied. In a multivariate analysis, it significantly correlated with outcome (PFS and OS, p = 0.004), and the loss of BAF47 immunoexpression appeared to be a significant independent prognostic factor (PFS, p = 0.033). We also identified clinical and histopathological parameters that correlated with prognosis. A new grading system combined with the quality of surgical resection could help classify patients to postpone radiotherapy in case of low risk. Targeted therapy and reirradiation at recurrence may be considered as potential therapeutic strategies.